Comparison of Schirmer and Tear Break Up Time (TBUT) Diagnostic Test of Dry Eye Following Phacoemulsification Cataract Surgery - Disty Andryani; Petty Purwanita; Anang Tribowo (Department of Opthalmology, Faculty of Medicine, Universitas Sriwijaya, 2019)
Abstract Background: Phacoemulsification is a technique of modern cataract surgery with smaller corneal incision than conventional techniques but uses various effects on springs that cause dry eye syndrome (DES). DES is a multifactorial defect of tears and ocular surfaces characterized by eye discomfort. Examination of DES can be done by examining Schirmer 1 and Tear Break Up Time (TBUT). Purpose: To determine the accuracy, sensitivity and specificity of the Schirmer test dan TBUT in postoperative patients with phacoemulsification techniques at the Rumah Sakit Khusus Mata Province of South Sumatra. Method: Diagnostic test has been done in order to the accuracy, sensitivity and specificity of the Schirmer test dan TBUT on DES in post operative cataract surgery with phacoemulsification techniques. This study has been conduct Schirmer 1 test and TBUT was done periodically from 1 week, 2 weeks and 1 month after cataract surgery. The data analysis has been done with diagnostic research by SPSS version 20.0 (SPSS, Inc Chicago, Illinois). Result: 40 study samples of post operative cataract surgery with phacoemulsification technique obtained by female sex with 22 out of samples were (55%), with an average age of patients between of 60-70 years.The accuracy of Shirmer 1 and TBUT test was 0,425 and the sensitivity value was 39.5% and also the specificity value was 100%. Conclusion: Schirmer 1 test and TBUT in patients of post cataract surgery with phacoemulsification techniques are specific (100%) but less sensitive (39,5%)